2016
DOI: 10.23937/2572-3308.1510012
|View full text |Cite
|
Sign up to set email alerts
|

Valsartan/Hydrochlorothiazide Induced Pemphigus Foliaceus

Abstract: Valsartan is an angiotensin II receptor blocker (ARB), a newer class of antihypertensives. Rarely some skin condition such as angioedema, urticarial, photosensitive rash, lichenoid eruption, pseudolymphomatous eruption and bullous pemphigoid, induced by valsartan have been

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…There is one case of valsartan and hydrochlorothiazide induced PF in the literature, and we cannot confidently disregard the possible effect. 9 However, the onset of the initial lesions after the first dose of vaccine and the exacerbation with new‐onset generalized lesions after the second dose suggest the association with mRNA vaccine. In our case, disease course was controlled easily with the proper treatment regimen.…”
Section: Figurementioning
confidence: 99%
“…There is one case of valsartan and hydrochlorothiazide induced PF in the literature, and we cannot confidently disregard the possible effect. 9 However, the onset of the initial lesions after the first dose of vaccine and the exacerbation with new‐onset generalized lesions after the second dose suggest the association with mRNA vaccine. In our case, disease course was controlled easily with the proper treatment regimen.…”
Section: Figurementioning
confidence: 99%
“…5 PF is the most common variant of druginduced pemphigus when caused by thiol containing drugs. 7 Although this patient is taking lisinopril, which contains an amide group, drug-induced pemphigus is more rare among angiotensin converting enzyme inhibitors other than captopril. Additionally, DISCUSSION metoprolol could be considered as a possible inciting drug as there are reports of beta-blockers causing drug-induced pemphigus.…”
mentioning
confidence: 94%
“…Additionally, DISCUSSION metoprolol could be considered as a possible inciting drug as there are reports of beta-blockers causing drug-induced pemphigus. 7 Bamlanivimab is favored as the most likely inciting agent in this case based on timeline of disease presentation. A review of 170 drug-induced pemphigus cases found that patients developed pemphigus within a mean of 154.27 days.…”
mentioning
confidence: 95%